Narrow-spectrum ß-lactam monotherapy in hospital treatment of community-acquired pneumonia: a register-based cohort study. (April 2017) - Rhedin, S.; Galanis, I.; Granath, F.; Ternhag, A.; Hedlund, J.; Spindler, C.; Naucler, P.
Abstract: Objectives: To assess the clinical effect of empirical treatment with narrow-spectrum ß-lactam monotherapy (NSBM) versus broad-spectrum ß-lactam monotherapy (BSBM) in non-severe community-acquired pneumonia (CAP). Methods: Hospitalized patients ≥18 years with CAP who received initial NSBM or BSBM, with a severity score according to CRB-65≤2 (C=confusion, R=respiratory rate >30/min, B=systolic blood pressure <90 mmHg or diastolic blood pressure ≤60 mmHg, 65= ≥65 years), in the Swedish Pneumonia Register from 2008 to 2011 were included. Primary outcome was 30-day mortality. Secondary outcomes were 90-day mortality, treatment at intensive care unit (ICU), and length of stay (LOS). Propensity score matching was performed to account for differences in baseline characteristics. Results: There were 5961 patients with CRB-65≤1 and 1344 patients with CRB-65=2. In the propensity score matched cohorts the 30-day mortality was 40/1827 (2.2%) with NSBM and 56/1827 (3.1%) with BSBM in CRB-65≤1, and 57/524 (10.9%) and 51/524 (9.7%), respectively, in CRB-65=2. No significant differences in 30-day mortality were observed between NSBM and BSBM in patients with CRB-65≤1 or CRB-65=2, OR 1.41 (95% CI 0.94–2.14) and 0.88 (95% CI 0.59–1.32), respectively. There was no significant difference in 90-day mortality. Patients who received BSBM were more often treated at ICU and had longer LOS. Conclusions: Empirical NSBM appears to be effective in the majority of hospitalized immunocompetent adults with non-severe CAP and should be further evaluated in randomized trials.